Measuring the Quality of God's Servants According to Acts 6:3 At the Surabaya City Tabernacle Pentecostal Church - Widi Prasetyo; Juanda Juanda; Surja Permana; Daniel Ari Wibowo (Theological Journal Kerugma, 2019)
Research on the Implementation of the Qualifications of God's Servants According to Acts 6:3 In the Pentecostal Church of Surabaya City Secretariat, wanted to find out the whereabouts of God's servants in the study according to Acts 6:3, especially in the scope of the Pentecostal Church Surabaya City Tabernacle. Specifically chapter 6:3, explains the essence of the solution to the problem, namely the selection of 7 servants of God. Obviously Dr. Luke reveals the criteria of God's servant who can be the solution to the problems that occur. At present, most Churches of God are more concerned with the physical buildings, facilities and infrastructure of the Church rather than thinking about how to get God's servants who can answer the needs of the congregation and the challenges of the times. What is even more concerning is that many of the Churches of God are procuring servants of God who only look at the side that can increase the image and popularity of the Church. So often the Church is.